A Comparative Study of Facial Indices of Maharashtrian Adults with Other Ethnic Group and Test For Reliability of Sexual Dimorphism - Sinchal Datta1 , Sawant V.G2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Variations in different craniofacial features is studied and documented using variousanthropometric techniques. The same depends on gender, race, ethnicity, nutritional and socioeconomicstatus of a person. So the human face and its variations has always been an object of interest for anatomists,forensic experts, anthropologists, plastic surgeons, maxillofacial surgeons, security experts and artists. Theaim of the present study was to identify the facial phenotypes of the Maharashtrian Males and Females.Availability of the Facial indices will augment the already available data of other studies.Materials and Methods: The present study was done on 505 (243 males, 262 females) pure bredMaharashtrian adults (3 generations on the maternal and paternal side of Maharashtrian origin)of the agegroup 18-60 years. The data was analyzed using MS excel Data Analysis Pak and Two-Sample t-test forUnequal Variances was done for facial indices of male and females to check for sexual dimorphism.Conclusion: The predominant facial type in Maharashtrian male is Mesoprosopic (37.86%) followedby Euryprosopic (29.22%) and that of female is Mesoprosopic (33.21%) and Euryprosopic (32.06%).This is similar to the results of studies on Indian males and females except Gujarati males who haveHypereuryprosopic face and Rajput males havingHyperleptoprosopic (long )face.A statistically significantdifference (p< 0.05). was obtained between facial indices of Maharashtrian males and females, which is akey to sexual dimorphism